South Asian transnational marriages in comparative perspective - CHARSLEY, KATHARINE; SHAW, ALISON (Global Networks, 2006)
Abstract This issue on South Asian transnational marriages brings diverse practices and networks into detailed ethnographic focus. Gender and agency are key themes explored in the collection, as well as the potential and actual transformation of gendered status resulting from marrying a migrant or joining a spouse overseas. The introduction identifies some common threads. Several articles challenge the assumption of wives' passivity in arranged marriages or in their joining husbands overseas, while one highlights the less-documented experiences of men who migrate to join wives working abroad. The collection also offers insights into the cultural and emotional reasons for such marriages, complementing analyses that stress strategic motivations, and noting the emotional consequences of separation and new household formations for the experiences of marriage and parenthood. Marriage emerges as an important means of producing and transforming transnational networks, while marriage practices and dynamics are themselves transformed in the process.
Keywords: 2000 à aujourd'hui; 2000-2009; anthropologie; approches et analyses; asie; asie du sud; cours; discipline; ethnographie; histoire et politique; mariage; migration; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques

Aspiration, reunification and gender transformation in Jat Sikh marriages from India to Canada - MOONEY, NICOLA (Global Networks, 2006)
In this article I explore marriage as a strategy of family migration among a transnational community of middle-class Jat Sikhs. Family reunification and status aspirations are examined as central concerns of the transnational movement of Jat Sikhs from India to Canada. It is argued that Jat Sikh transnationalism and gender are mutually-constitutive: migration strategies can construct women, as well as men, as agents of marital citizenship, and in facilitating migration, transnational marriage may transform practices and notions of gender and status. The article is based on preliminary ethnographic research among Jat Sikh brides in Toronto and Vancouver, and forms part of a larger study of gender, modernity and identity in Indo-Canadian Jat Sikh marriages.
Keywords: amériques; anthropologie; approches et analyses; asie; canada; colombie-britannique; cours; discipline; famille; histoire et politique; inde; intersectionnalité; justice sociale; mariage; mariages transnationaux; migration; ontario; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques; toronto; vancouver

The nature of gender: work, gender, and environment - Nightingale, Andrea (Environment and Planning D: Society and Space, 2006)
Le genre est depuis longtemps reconnu comme important dans les questions environnementales, mais la manière de conceptualiser le lien entre genre et environnement fait l’objet de nombreux débats. Les théories féministes sur les femmes et le genre ont évolué, tout comme les conceptualisations sur le genre et l’environnement, ce qui a donné lieu à un débat clé au sein de l’écoféminisme et des littératures associées sur la question de savoir s’il existe une relation essentielle ou contingente entre les femmes et les environnements naturels. En géographie, la plupart des écologistes politiques partent du principe que le lien entre genre et environnement est une relation contingente, et étudient donc la manière dont les relations de genre sont saillantes dans la construction symbolique et matérielle des questions environnementales. Dans cet article, je cherche à m’appuyer sur ce travail et à soulever à nouveau la question de la manière dont le genre est conceptualisé par rapport à l’environnement. Je commence par passer brièvement en revue certains des travaux qui ont été réalisés sur le genre et l’environnement, puis je m’inspire du féminisme post-structural pour suggérer que le genre lui-même a été sous-théorisé dans les travaux sur l’environnement. Une fois que le genre est reconceptualisé en tant que processus, la relation dynamique entre le genre, l’environnement et d’autres aspects de la vie sociale et culturelle peut être mise en évidence. Il en ressort que les écologistes politiques doivent examiner la question du genre au-delà du foyer et de la communauté, et reconceptualiser le lien entre le genre et l’environnement. Une étude de cas sur la foresterie communautaire au Népal est utilisée pour illustrer l’importance d’interroger les processus par lesquels les relations entre les sexes deviennent saillantes et sont reproduites symboliquement et matériellement.
Keywords: approches et analyses; asie; discipline; environnement; géographie; histoire et politique; népal; politique écologique; post-structuralisme; projet charge mentale; régions géographiques; sciences humaines; sociologie; thématiques; écoféminisme